A Simple Four Quadrants Model to Monitor the Performance of Local Governments - Danilo Ballanti; Roberto Dispotico; Francesco Porcelli; Francesco Vidoli (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper, conducted as part of the research activities of SOSE S.p.A., develops a simple and innovative model to evaluate the performance of local government in the provision of local public services. The model employs a reduced set of information and fewer assumptions than traditional techniques such as Data Envelopment Analysis and Stochastic Frontier Analysis. The main idea is to base the model on the joint graphical analysis of standard expenditures needs and standard level of services both estimated using a reduced form approach derived from a general theoretical framework based on the interaction between the demand and the supply for local public services. Data about social care services provided by Italian municipalities in 2010 are used to test the model.
Keywords: H72; H77; H83; 330; standard level of services; standard expenditure needs; performance; local governments; municipality; Italy